Design and test of the anti-skid system for self-propelled high-stem crop sprayers - Wen, Haojun; Liu, Xinyue; Yi, Zhetian; Li, Zhongxiang (International Journal of Agricultural and Biological Engineering, 2024)
Aiming at the problem of skidding in the operation of a self-propelled high-stem crop sprayer due to uneven road surface and uneven distribution of soil cohesive force, This study proposed a four-wheel drive hydraulic anti-skid control system based on RTM valve. Through theoretical analysis of control components such as the RTM valve and steering cylinder, the control model of the anti-skid drive system of the spray machine is established, and the simulation test is carried out in Matlab/Simulink. The simulation results show that the slip rate of the anti-skid drive system based on the PID control strategy is controlled below 0.05, and the RTM valve keeps the driving pressure of the system basically stable. In order to verify the reliability of the simulation results, the designed drive anti-skid control system was carried out on a spray machine for the field test. The experimental results show that the slip rate of the drive anti-skid system decreases from 86.7% to 1.25% when the anti-skid function is turned on, indicating that the designed drive anti-skid system has good anti-skid performance. Keywords: self-propelled sprayer, high-stem crops; drive anti-skid, PID control, Matlab, Simulink DOI: 10.25165/j.ijabe.20231606.5825 Citation: Wen H J, Liu X Y, Yi Z T, Li Z X. Design and test of the anti-skid system for self-propelled high-stem crop sprayers. Int J Agric & Biol Eng, 2023; 16(6): 20–27.